PENERAPAN KOMUNIKASI PEMASARAN TERPADU (IMC) DALAM MEMPROMOSIKAN USAHA RITEL: STUDI KASUS KEPULAUAN RIAU 2020–2025 - Kremer, Hendri; Heryenzus, Heryenzus; Suali, Suali (JURSIMA, 2026)
Border areas such as the Riau Islands have unique characteristics that influence retail marketing communication strategies, mainly due to their strategic position among cross-border trade, cultural, and tourism flows. This study aims to examine how modern retail business actors in the Riau Islands apply an integrated marketing communication mix (IMC) in reaching and retaining local consumers during the 2020–2025 period. Using a descriptive qualitative approach with a dual case study strategy, data were obtained through in-depth interviews, field observations, and documentation of retail promotion activities in the cities of Batam, Tanjungpinang, and Bintan. The results of the study revealed six main themes that marked the IMC implementation pattern, namely the synergy between digital and traditional channels, the dominance of direct sales promotion, the personalization of community-based communication, the importance of public relations and brand storytelling, the role of visual communication, and challenges in measuring the effectiveness of strategies. This research shows that the success of retail marketing communications in border areas is highly dependent on adaptability to multicultural local contexts as well as consistent and relevant cross-media messaging integration. The main contribution of this research lies in the enrichment of the theoretical perspective of IMC in a geographical context that has been underexplored, as well as the provision of an analytical framework that can be used by practitioners and policymakers to develop more effective and sustainable communication strategies in border areas